A Comprehensive Review of Therapeutic Approaches Available for the Treatment of Dermatitis - Singh, Apoorva; Nimisha (Recent Patents on Nanotechnology, 2022)
Background: Dermatitis or eczema is a prevalent skin disorder worldwide and is also very common as a pediatric inflammatory skin disorder. Its succession gets worse with the multiple comorbidities which exhibit mechanisms that are poorly understood. Its management further becomes a challenge due to the limited effective treatment options available. However, the Novel Drug Delivery Systems (NDDS) along with new targeting strategies can easily bypass the issues associated with dermatitis management. If we compare the active constituents against phytoconstituents effective against dermatitis then phytoconstituents can be perceived to be more safe and gentle. Objective: Administration of NDDS of plant extract or actives displays improved absorption behavior, which helps them to permeate through lipid-rich biological membrane leading to increased bioavailability. The newer efficient discoveries related to eczema can face various exploitations. This can be intervened by the subjection of patent rights, which not only safeguard the novel works of individual(s) but also give them the opportunity to share details of their inventions with people globally. Conclusion: The present review focuses on the available research about the use of nanoformulations in the topical delivery. It further elaborates the use of different animal models as the basis to characterize the different features of dermatitis. The review also highlights the recent nanoformulations which have the ability to amplify the delivery of active agents through their incorporation in transfersomes, ethosomes, niosomes or phytosomes, etc.
Keywords: patent